Effects of environmental variables on midsummer dinoflagellate community in the Neva Estuary (Baltic Sea) - Mikhail Golubkov; Vera Nikulina; Sergey Golubkov (Oceanologia, 2019)
Summary: Dinoflagellates account for most of the harmful phytoplankton species but relatively little is known about the specific responses of different species to environmental variables. 21 dinoflagellate species were recorded in the plankton of the Neva Estuary since the mid-19th century. 14-year long data of midsummer dinoflagellate biomass was statistically analyzed in the Neva Estuary to show the changes in dinoflagellate species in relation to environmental factors. Biomasses of Dinophysis norvegica (Clapared & Lachmann 1859), Prorocentrum lima ((Ehrenberg) F.Stein 1878) and Peridinium aciculiferum (Lemmermann 1900) had very similar positive relationships with salinity, temperature, phosphorus and suspended particulate organic matter concentrations while the biomass of the other common species Peridinium cinctum ((Müller) Ehrenberg 1832) and Peridinium sp. mostly showed quite opposite trends. Climate fluctuations leading to changes in the environmental variables could significantly affect the composition and productivity of the dinoflagellate community. Biomass of Glenodinium sp. and Peridinium sp. positively correlated with primary production and biomass and chlorophyll a concentration, but did not show a positive relationship with phosphorus. This may be due to the fact that these species in the conditions of the Neva Estuary, apparently, are more consumers than producers of organic matter, feeding on algae and cyanobacteria of phytoplankton. Therefore, to interpret the relationships between the dinoflagellate biomass and environmental variables one should take into account that the species of this group is characterized by mixotrophy and, consequently, their biomass may depend not only on the conditions of autotrophic, but also heterotrophic nutrition. Keywords: Gulf of Finland, Phytoplankton, Mixotrophy, Eutrophication, Climate change